Blockchain-Based Automatic Tracking and Extracting Construction Document for Claim and Dispute Support - Kim, Eu Wang; Park, Min Seo; Kim, Kyoungmin; Kim, Kyong Ju (KSCE journal of civil engineering, 2022)
During a long-term construction project, numerous stakeholders participate and collaborate with each other. In such scenario, the processes of creating, storing, and managing project documents are highly complicated. Due to the nature of the construction projects, problems arise in document management such as loss of documents and difficulties in tracking, which can result in claim failure and huge damage. This study proposes a method to efficiently record, search, and manage construction documents that can protect legal rights in preparation for claims/disputes. This study designed a system that can generate, transfer, and synchronize blocks based on email communication whenever an event occurs. It also provides functions such as document search, history tracking, automatic extraction of related document, and authenticity verification for document management. The findings of the study have established that reliability of documents is secured during the recording, storing, and managing processes, and thus claim- and dispute-supporting tasks are supported.